The physiological responses of salinity stressed tomato plants to mycorrhizal infection and variation in rhizosphere carbon dioxide concentration - Lintnaar, Melissa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.